Crack initiation and growth in shape memory alloys - Mutlu, Fatma. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
The aim of this thesis is to study the crack initiation and growth in shape memory alloys (SMAs), with emphasis given to martensitic transformation in front of the crack tip and non- transforming phase interactions along the crack path. In the first part, the effect of phase transformation on the fracture of polycrystalline NiTi SMAs is examined to introduce the complexities encountered in transforming materials. Fracture experiments are conducted at two different loading rates, and crack initiation and growth are monitored: In all samples, the crack starts and grows at a straight angle from the notch. Later, the J-Integral is evaluated experimentally and numerically. At a low loading rate the driving mechanism for resistance to fracture is phase transformation, but at a higher loading rate heat dissipation becomes more prominent due to higher magnitude of latent heat release. In the second part, crack initiation and growth in single-crystal CoNiAl SMAs are investigated using cyclic loading experiments. In crack growth tests, cracks initiate and grow at an angle similar to the martensite band angle of tensile specimens. Crack initiation angles of superelastic CoNiAl samples are calculated analytically and numerically, and the results are found to be in good agreement with the experiments. Stress intensity factors (SIFs) and crack growth rates (da/dN) are calculated for growing cracks, the behavior of which are investigated by examining the test samples with an optical microscope: When non-transforming secondary phase regions are encountered, cracks slow down/stop and SIFs increase/decrease. Overall, it is found that the non-transforming phase acts as a barrier against crack growth and improves the fracture resistance of the SMA. The results of the study underline the importance of including the effects of phase transformation and non- transforming microstructural barriers for a better understanding of the fracture behavior of SMAs.
Keywords: Materials -- Cracking.; Shape memory alloys.